Pengembangan Media Pembelajaran Modeling melalui Video dalam Peningkatan Kemampuan Toilet Training pada Anak Tunagrahita - Ima Sukmawati; Elis Noviati (Jurnal Keperawatan Silampari, 2021)
This study aims to improve the ability of toilet training in mentally retarded children through video modeling. The research method used a pre-experimental design with a one-group pre-test and post-test design. The results showed the effect of video media modeling on the toilet training ability of mentally retarded children, with an average increase of 1.59. The Wilcoxon test shows a p-value of 0.001. In conclusion, video media modeling has an effect on the toilet training ability of mentally retarded children. Keywords: Children with Mental Retardation, Video Media Modeling, Toilet Training